A Study on the Profitability and Financial Position of Information Technology Companies in India During The Post Liberalization Period - Sundaram, N.; Sudalaimuthu, S. (Indian Journal of Finance, 2009)
The corporate sector is increasingly depending on external sources for meeting its funding requirements. Thee appears to be growing preference for direct financing (Equity and Debt) instead of indirect financing from the external sources3 like bank loan etc. The palpable reason is that value of the firm can be increased or a judicious mix of debt and equity capital can reduce the cost of capital. So the manner in which the over all cost of capital reacts to changes in capital structure and solvency, are required to be measured to know the shareholder’s value. To obtain better understanding of the firm’s position and performance of Information Technology Companies, the ratio analysis shall be considered as a tool for analysis of return on invested capital, profitability, liquidity, asset utilization and efficiency, capital structure and solvency etc., rather than as an end in itself. The financial statements provide information about the financial positions of an enterprise that is useful to a wide range of users in making economic decisions. The significant role of this research is to ensure the perspicuous comparative study of these Information Technology companies by pursuing the research in two Categories by Ratio analysis and basic descriptive statistics respectively. Ratio analysis is a widely - used tool for financial analysis. It enables the shareholders to spot trends in a business and to compare its performance and condition with the average performance of similar businesses in the same industry. This research uses a selection of ratios to examine a firm’s financial strength and weakness and to provide the essential foundation for financial decision-making and planning.